More listening: Philosophy as bluesology - Heter, Thunder Storm (South African journal of philosophy, 2025)
This essay studies the work of Mabogo More, arguing that More is a philosopher of listening. The essay deals with More's critique of white liberalism, arguing that More offers several varieties of critiques of being-a-white-philosopher-in-the-world.